Stylistic Features in Sapardi Djoko Damono’s Poetry Anthology Hujan Bulan Juni and Their Relevance as Teaching Materials for Middle School - Salma Faqiha Dinayati; Ali Imron Al-Ma’ruf (Faculty of Humanities, Universitas Jenderal Soedirman, 2026)
This study aims to identify and interpret stylistic devices and their meanings in Sapardi Djoko Damono’s anthology Hujan Bulan Juni and to analyze its potential as a literary teaching resource at the junior high school level. The analysis in this study focuses on six stylistic aspects according to Al-Ma'ruf (2022), namely sound style (phonemes), word style (diction), sentence style (syntax), discourse style, figurative language, and imagery. This study employs a qualitative descriptive approach using document analysis on 17 poems in the anthology Hujan Bulan Juni, yielding 17 stylistic data points. The analysis was conducted through heuristic and hermeneutic readings based on Michael Riffaterre’s semiotics to uncover the poems’ meanings, while the assessment of their relevance as teaching materials referred to Rahmanto’s (1988) criteria, which encompass linguistic, psychological, and cultural background aspects. The results of the study show that these six stylistic aspects shape the aesthetic character of the poetry, which is simple, reflective, and rich in meaning. A hermeneutic reading reveals that these stylistic devices not only function as aesthetic elements but also represent the meanings of patience, solitude, loyalty, the search for identity, and reflections on life. The research findings also indicate that the use of communicative language and the depth of meaning in the poems make this anthology a potential resource for teaching literature in junior high schools, in accordance with linguistic, psychological, and cultural criteria.